2011
DOI: 10.1111/j.1365-2516.2011.02600.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with Optivate®, high‐purity factor VIII (FVIII) product with von Willebrand factor (VWF) in young children with haemophilia A

Abstract: Optivate® is a high-purity FVIII/VWF product. Its safety, tolerability and efficacy in subjects ≥ 12 years have been demonstrated. This study was undertaken to assess Optivate® in children with haemophilia A. Twenty-five children, including one PUP (previously untreated patient), aged 1-6 years (mean 4.67 years) were treated with Optivate® for 26 weeks. Inhibitors were assessed every 3 months and viral status at the study start and end. Prophylaxis was used by five boys and on demand by twenty. The mean number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Types and brands of factor concentrates administered in the selected studies are shown in Table 1. Forty‐five studies [20–64] reported patients with HA receiving FVIII concentrates (Table 2), 15 studies [65–79] patients with HB treated with FIX concentrates (Table 3) and 11 studies [80–90] VWD patients treated with VWF containing products (Table 4). Owing to the peculiar pathophysiologic situation, six studies [91–96] reporting haemophilia patients who had central venous access devices (CVAD) in order to facilitate long‐term regular concentrate administration (prophylaxis, immune tolerance induction) were analyzed separately (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Types and brands of factor concentrates administered in the selected studies are shown in Table 1. Forty‐five studies [20–64] reported patients with HA receiving FVIII concentrates (Table 2), 15 studies [65–79] patients with HB treated with FIX concentrates (Table 3) and 11 studies [80–90] VWD patients treated with VWF containing products (Table 4). Owing to the peculiar pathophysiologic situation, six studies [91–96] reporting haemophilia patients who had central venous access devices (CVAD) in order to facilitate long‐term regular concentrate administration (prophylaxis, immune tolerance induction) were analyzed separately (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Of them, 24 were further excluded because the relevant data were unavailable or because analyzed patients were included in other published studies or because the study design did not permit a pooled analysis of the data. Finally, 27 studies with usable information (15 prospective, 11 retrospective and one retrospective/prospective), published between 1996 and 2011, were included in this systematic review [8,10,12,14–37], as reported in Table 1. Statistical analysis was performed using the chi‐square test.…”
Section: Characteristics and Results Of Studies Included In The Systmentioning
confidence: 99%
“…Overall Optivate was well tolerated. There have been no reports of inhibitor development to FVIII and/or VWF with Optivate in this study or any of the other clinical studies [2,[6][7][8][9] or from postmarketing experience to date.…”
mentioning
confidence: 93%
“…Optivate is licensed in several countries worldwide for the treatment of Haemophilia A in both adults and children [6][7][8][9]. This letter reviews data from a BPL sponsored single centre, randomized pharmacokinetic (PK) study comparing Optivate and Haemate P (also known as Humate P) in VWD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation